Restoration of Gypsicolous Vegetation on Quarry Slopes: Guidance for Hydroseeding under Contrasting Inclination and Aspect. (24th May 2017) - Ballesteros, Miguel; Cañadas, Eva María; Marrs, Rob H.; Foronda, Ana; Martín‐Peinado, Francisco José; Lorite, Juan
Abstract: The establishment of gypsicolous vegetation of high conservation value on land impacted by quarrying requires restoration measures to overcome constraints imposed by the new landforms created in the process. The aim of this study was to assess the suitability of three standard hydroseeding methods to restore gypsicolous vegetation on quarry spoil slopes under a dry Mediterranean climate. The treatments were as follows: paper cellulose mulch, paper cellulose mulch + organic blanket, and wood fibre mulch, compared against a control. These treatments were tested on two slopes (10–15% vs 60–65%) and two contrasting aspects (north vs south). We evaluated the cover of all plant species 2·8 years after treatment, assessing both target gypsicolous species and non‐target species. Our results showed strong compositional and cover differences between hydroseeded and control plots. Control plots had a low cover of target species with a vegetation composed of early‐successional species that had the potential to hinder target species establishment over time. All hydroseeding treatments improved target vegetation cover, with wood fibre performing best in most situations studied here, alternatives being the cheaper but less effective paper mulch on shallow slopes, or the more expensive paper mulch + blanket on steep slopes in case of high erosion risk. Shallow and southern‐steep slopes were more suitable for the recovery of gypsum vegetation by hydroseeding, compared to northern‐steep slopes where non‐target species developed more readily outcompeting target species. These results will help to guide management decisions to restore gypsicolous vegetation by hydroseeding in disturbed gypsum habitats. Copyright © 2017 John Wiley & Sons, Ltd.